2021
DOI: 10.1089/regen.2021.0016
|View full text |Cite
|
Sign up to set email alerts
|

Prime Editing, a Novel Genome-Editing Tool That May Surpass Conventional CRISPR-Cas9

Abstract: Background: Genome editing mediated by clustered regularly interspaced short palindromic repeat -CRISPR-Cas-was first reported using cell lines in 2012, and since then, its applications in other systems have steadily increased. However, this approach still needs improvement and optimization. Prime Editing (PE) was originally proposed by Anzalone and colleagues in 2019, who showed significant lower rates of "off target" effects compared to conventional CRISPR-Cas9. Objectives: In this review, we describe and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
(55 reference statements)
0
9
0
2
Order By: Relevance
“…Prime Editing may also introduce undesirable mutations and there are limitations in terms of large DNA insertions. Hence further studies are required to establish the efficiency of the Prime Editing tool as a promising tool for cancer therapeutics with minimized drawbacks [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prime Editing may also introduce undesirable mutations and there are limitations in terms of large DNA insertions. Hence further studies are required to establish the efficiency of the Prime Editing tool as a promising tool for cancer therapeutics with minimized drawbacks [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prime Editing is capable of overcoming major drawbacks of chemotherapeutic and radiation-based strategies. Prime Editing uses a site-specific mutagenesis approach and presents high efficiency and precision in terms of genome editing [ 1 ]. Anzalone et al demonstrated Prime editing as one of the most promising tools for genome editing.…”
Section: Role Of Prime Editing In Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…This review article describes the details of the prime editing tool, which has advantages over existing CRISPR/Cas systems. Although many excellent reviews are available highlighting the importance of this tool, [17][18][19][20] this is the first comprehensive review on this system utilized for the modifications of the genome in plants and mammalian cells. Next, we draw inroads and insights into the future application of the prime editing tool in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…PE is an innovative site-specific gene editing technique that evolved as an advancement of the CRISPR-Cas and base editing techniques. The PE has higher specificity compared to the traditional genome editing techniques because it relies on the single-stranded DNA nick created by Cas-nuclease instead of double-strand breaks (Ochoa-Sanchez et al, 2021). PE can directly incorporate exogenous edits at the target site by using a PE gRNA (pegRNA), which not only consists of single-guide RNA (sgRNA) but also a mutant repair template with a priming site for reverse transcriptase (RT).…”
Section: Introductionmentioning
confidence: 99%